The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1158/0008-5472.sabcs12-p3-06-24
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-06-24: Early activation of IFN/STAT signaling in tumor cells of patient-derived triple negative breast cancer xenografts predicts tumor sensitivity to chemotherapy

Abstract: Triple negative breast cancer (TNBC) is a tumor subtype characterized by the absence of overexpressed estrogen receptor-alpha (ER), progesterone receptor (PR), and HER2 receptor, encoded by ERBB2, a known proto-oncogene. This type of tumors account for approximately 15–25% of breast cancers at diagnosis, and is one of the most aggressive subtypes, with 77% of patients that live free of disease 5 years post-diagnosis. One of the most reliable predictive markers of patient outcome is the pathological complete re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Identification of IFN/STAT signaling as a predictor of therapeutic response to cyclophosphamide chemotherapy in triple negative breast cancer[91]…”
Section: Figurementioning
confidence: 99%
“…Identification of IFN/STAT signaling as a predictor of therapeutic response to cyclophosphamide chemotherapy in triple negative breast cancer[91]…”
Section: Figurementioning
confidence: 99%
“…The genes were chosen from literature review on the basis of their being identified as (i) possible prognostic factors in residual disease at protein (4,(6)(7)(8)(9)(10) or mRNA level (11), (ii) as significantly up-or downregulated, but of unknown prognostic value in residual disease (12)(13)(14)(15)(16)(17)(18)(19)(20), (iii) as predictive of chemotherapy resistance (6,11,16,19,(21)(22)(23)(24)(25)(26)(27)(28)(29), and/or (iv) identified as possible prognostic factors over several previous datasets (26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In addition to the previously established prognostic factors ESR1 and ERBB2, the genes were also chosen to represent different pathways and biological processes of known implication in tumor progression or response to therapy, such as stemcellness (ALDH1A1, CD44, and STAT3), proliferation (TOP2A, MKI67, and AURKA), apoptosis (BCL2, BCL2L1, and PAWR), immunologic response (CD3D, CXCL13, and STAT1), epithelial-to-mesenchymal transition (EMT; SNAI1, SNAI2, SOX9, and TWIST), stromal activation (DECORIN, ...…”
Section: Introductionmentioning
confidence: 99%